CsxWO3@NBs as a Multi-Image Guided Photothermal/Photodynamic Combination Therapy Platform for the Treatment of Hepatocellular Carcinoma - Wang C; Wang X; Tian Y; Tian H; Chen Y; Wu B; Cheng W (International Journal of Nanomedicine)
Chunyue Wang, Xiaodong Wang, Yuhang Tian, Huimin Tian, Yichi Chen, Bolin Wu, Wen Cheng Department of Ultrasound, Harbin Medical University Cancer Hospital, Harbin, People’s Republic of ChinaCorrespondence: Wen Cheng, Department of Ultrasound, Harbin Medical University Cancer Hospital, No. 150, Haping Road, Nangang District, Harbin, 150081, People’s Republic of China, Tel +86 13313677182, Fax +86 451 85718392, Email chengwen@hrbmu.edu.cnPurpose: Effective cancer treatment relies on the precise deployment of clinical imaging techniques to accurately treat tumors. One highly representative technology among these is multi-imaging guided phototherapy. This work introduces a new and innovative theranostic drug that combines near-infrared (NIR) irradiation-induced photodynamic therapy (PDT) and photothermal therapy (PTT) to treat malignancies. Moreover, it can be utilized as a contrasting substance for X-ray computed tomography (CT) imaging and contrast-enhanced ultrasound (CEUS) to aid in the administration of therapy.Methods: Cesium tungsten bronze nanobubbles (CsxWO3@NBs) were constructed via a water-controlled solvothermal synthesis and thin film hydration of phospholipid. Various methods, including dynamic light scattering, transmission electron microscopy, and X-ray photoelectron spectroscopy, were used to analyze and describe the size, shape, and chemical characteristics of the nanoparticles. In this study, hepatoma cell lines HepG2 and HUH7 were employed in vitro, and xenotransplantation mouse models were used to assess their antitumor effects. A series of in vitro and in vivo trials were conducted to assess the effectiveness of combining photodynamic and photothermal therapies, as well as using CEUS and CT imaging.Results: The CsxWO3@NBs exhibit photothermal effects and the generation of reactive oxygen species (ROS) under laser irradiation, thereby enabling effective photothermal and photodynamic combinatorial therapy. Following combined treatment, the activity and invasive capacity of hepatocellular carcinoma cells were markedly diminished, the development rate of the tumor was noticeably reduced, and the level of biological toxicity was low. Additionally, CsxWO3@NBs possess the capacity to serve as both a CT imaging agent and a contrast-enhanced ultrasound agent.Conclusion: CsxWO3@NBs represent a promising theranostic agent for image-guided cancer therapy.Keywords: photodynamic therapy, photothermal therapy, imaging, apoptosis, hepatocellular carcinoma